SITUATIONS THAT ARISE DUE TO THE LACK OF DRINKING WATER TODAY - Karshiyeva D.R. (World Scientific Research Journal, 2025)
Abstract. Climate warming and inappropriate use of water resources can cause a drinking water crisis. This can not only endanger the lives of millions, but also cause dangerous socio-economic consequences.